Storyworlds: naughty joe - Gaines, Keith (Heinemann UK, 2009)
In "Naughty Joe," the mischievous protagonist stirs up chaos in his quaint town, pushing the boundaries of fun and mischief. As he navigates the consequences of his antics, Joe learns valuable lessons about friendship, responsibility, and the importance of balance between fun and respect.